Molecular mechanisms of gastric epithelial cell adhesion and injection of CagA by Helicobacter pylori - Backert, Steffen; Clyne, Marguerite; Tegtmeyer, Nicole (Cell Communication and Signaling, 2011)
Helicobacter pylori is a highly successful pathogen uniquely adapted to colonize humans. Gastric infections with this bacterium can induce pathology ranging from chronic gastritis and peptic ulcers to gastric cancer. More virulent H. pylori isolates harbour numerous well-known adhesins (BabA/B, SabA, AlpA/B, OipA and HopZ) and the cag (cytotoxin-associated genes) pathogenicity island encoding a type IV secretion system (T4SS). The adhesins establish tight bacterial contact with host target cells and the T4SS represents a needle-like pilus device for the delivery of effector proteins into host target cells such as CagA. BabA and SabA bind to blood group antigen and sialylated proteins respectively, and a series of T4SS components including CagI, CagL, CagY and CagA have been shown to target the integrin β§ssub§1 §esub§receptor followed by injection of CagA across the host cell membrane. The interaction of CagA with membrane-anchored phosphatidylserine may also play a role in the delivery process. While substantial progress has been made in our current understanding of many of the above factors, the host cell receptors for OipA, HopZ and AlpA/B during infection are still unknown. Here we review the recent progress in characterizing the interactions of the various adhesins and structural T4SS proteins with host cell factors. The contribution of these interactions to H. pylori colonization and pathogenesis is discussed. © 2011 Backert et al; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up
Keywords: adherence; adhesin; Helicobacter pylori; integrin; receptor; signalling; type IV secretion